Karawitan Composition Atma Prasangsa | Komposisi Karawitan Atma Prasangsa - I Gede Mahendra Adi Putra; Ni Wayan Masyuni Sujayanthi (GHURNITA: Jurnal Seni Karawitan, 2024)
Atma Prasangsa is the process of the journey of the spirit or soul from when a person is still alive until he reaches moksha. In everyday life, the stylist relates Atma Prasangsa's meaning to the stylist's personal experience, who lost a grandfather named I Wayan Ngarda. Seeing this phenomenon, the arranger appointed Atma Prasangsa as a musical composition title in the form of percussion creations. Due to limited tools and support from partners due to the Bali Art Festival event, the stylists decided to borrow the Angklung gamelan as a medium for saying in this work at Banjar Kayutulang Canggu. Atma Prasangsa work is intended as a tribute to the late grandfather of the stylist himself. Gamelan Angklung is classified as a gamelan with a four-tone selendro barrel. This work used the structure of the parts and decided to use five for the protrusion that the stylist made to focus the stylist's idea into the work, namely in part two and part four, where the part describes sadness and is sincere about the departure of the stylist's grandfather. The duration of the whole arable is around 12 minutes. Hopefully, with this work, the community can follow the reforms in karawitan art, especially in the Angklung gamelan.